"How To" manual for informing crop wild relative conservation and use benefit-sharing mechanism design and implementation - Drucker, Adam G.; Khaki Mponya, Nolipher; Grazioli, Francesca; Maxted, Nigel; Brehm, Joana Magos; Dulloo, Mohammad Ehsan (2022)
The fair and equitable sharing of the benefits arising out of the utilization of genetic resources is one of the three objectives of the Convention on Biological Diversity (CBD); while under the International Treaty on Plant Genetic Resources for Food and agriculture (ITPGRFA) Article 9.2b addresses the right to equitably participate in sharing benefits arising from the utilization of PGRFA. Benefits may include monetary and non-monetary benefits, including but not limited to those listed in the Annex of the Nagoya Protocol.